Algorithmic Governmentality and the Construction of Political Truth - Athira Zahroh Firdausi Ramadhani (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2026)
The shift in political campaigning style ahead of the 2024 election has been largely driven by technological advancements. Candidates increasingly utilised social media, particularly TikTok, to attract the attention of Gen Z and Millennial voters. This study aims to examine how the TikTok algorithm functioned as a political marketing strategy for the Prabowo–Gibran pair and to analyse the power relations embedded within their digital campaign. Employing a qualitative methodology the research uses content analysis techniques underpinned by Michel Foucault’s perspective on discourse theory. Were gathered through a literature review and observation of TikTok content. While content analysis identifies specific campaign patterns and strategies, the Foucauldian lens reveals the power relations operating within algorithmic mechanisms. The findings demonstrate that the Prabowo–Gibran campaign used the ‘gemoy’ dance, viral jingles, and AI-generated cartoons to engage young voters. Through discourse practices that shape a new ‘regime of truth’, the ‘reversal to real’ strategy successfully transformed Prabowo’s public persona from a stern military figure into a populist one. Furthermore, the power relations within Jokowi’s political network were widely disseminated via TikTok, with algorithms serving as a ‘technology of power’ that governed voter preferences and contributes to the pair’s victory.